The effectiveness of Pearson My English lab platform in the EFL learning process at PUCE-I in A1 level - Calderón Lascano, Martín Israel (2024)
Despite the growing popularity of online platforms for teaching English, there is a need to critically examine and assess these platforms' effectiveness in addressing potential challenges. This research explores the effectiveness of Pearson's My English Lab platform in enhancing the English as a Foreign Language (EFL) learning process at Pontificia Universidad Católica del Ecuador - Ibarra (PUCE-I) for students at the A1 level. The study employs a mixed-methods approach, combining quantitative and qualitative data collection and analysis. The quantitative data is gathered through surveys, while interviews collect qualitative data.